Application of Sorption Analysis in the Study of Various Nanomaterials Used in Electronics Depending on their Composition and Production Conditions - A. S. Lenshin; E. V. Maraeva (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. At present, sorption methods of analysis, including the thermal desorption of inert gases, are widely adopted to characterize the porous structure parameters of nanomaterials having a wide range of applications. Nitrogen thermal desorption belongs to the group of nondestructive techniques that provide a rapid analysis of the following parameters exhibited by nanomaterials: specific surface area, average particle size, mesopore size distribution, as well as the presence or absence of micropores in the system. In this work, mesoporous silicon and calcium hydroxyapatite powders are selected as the objects of research. Since modern interference optical filters are cumbersome and expensive to use, meso- and nanoporous silicon nanostructures are of interest in the implementation of filters for fiberoptic communication systems. Hydroxyapatite can potentially provide high corrosion resistance while posing no risk of toxicity to the environment. In addition, anticorrosion hydroxyapatite coatings are of decisive importance for the practical application of magnesium alloys used to reduce the weight of vehicles, aircraft, and electronics housings.Aim. To consider the application of the thermal desorption of inert gases, specifically nitrogen thermal desorption, in the study of the porous structure parameters of nanomaterials having various compositions on the example of mesoporous silicon and hydroxyapatite.Materials and methods. In this work, the thermal desorption of inert gases and capillary condensation were applied to study the porous structure parameters of hydroxyapatite and porous silicon powders. In particular, the nitrogen thermal desorption method was implemented using a Sorbi MS instrument equipped with a Sorbi Prep sample preparation station.Results. Recommendations are provided on choosing the mass of the adsorbent material required for the study, the sample preparation conditions, as well as the relative partial pressure range of the gas adsorbate. The selected sample types were found to lack a micropore system in the structure. Finally, the dependence of the specific surface area of hydroxyapatite powders and the parameters of its mesoporous structure on heat treatment conditions was analyzed.Conclusion. The study of nitrogen adsorption and capillary condensation allows the porous structure parameters of hydroxyapatite and porous silicon to be reproduced, which is of great importance for their use in medicine and radio electronics as anticorrosion coatings, as well as for the implementation of optical filters.